Hubungan Kecerdasan Spiritual dengan Perilaku Keagamaan di Madrasah Aliyah Negeri 4 Bogo - Siti Nur Kholisaturrizqi[; Rusdi Kasman; Putri Ria Angelina (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This study aims to 1) Determine the spiritual intelligence of class XI IPS students at MAN 4 Bogor; 2) Find out the religious behavior of class XI IPS students at MAN 4 Bogor; and 3) Find out whether there is a relationship between spiritual intelligence and the religious behavior of class XI IPS students at MAN 4 Bogor. Data collection techniques using questionnaires and documentation. The research instrument to obtain data in this study consisted of a questionnaire guide and documentation. The data analysis technique uses categorization and product moment. The results of the study show that there is a significant correlation between the spiritual intelligence variable (X) and religious behavior (Y) in class XI Social Studies at Madrasah Aliyah Negeri 4 Bogor where the t-count is 5.822 with a significant value of 0.000, then t-count 5.822 > t-table 1.665 so Ho is rejected and Ha is accepted. Keyword: Spiritual Intelligence, Religious Behavior